Knowledge and beliefs about dietary inorganic nitrate among UK-based nutrition professionals: development and application of the KINDS online questionnaire. Issue 10 (31st October 2019) - Shannon, Oliver M; Grisotto, Giorgia; Babateen, Abrar; McGrattan, Andrea; Brandt, Kirsten; Mathers, John C; Siervo, Mario
Abstract : Objectives: To examine knowledge and beliefs about the biological roles of dietary inorganic nitrate in UK-based nutrition professionals, and to explore potential differences by participants' education level. Setting: An online questionnaire was administered to UK-based nutrition professionals, exploring knowledge and/or beliefs across five areas: (1) health and performance effects of nitrate; (2) current and recommended intake values for nitrate; (3) dietary sources of nitrate; (4) methods of evaluating nitrate intake and (5) nitrate metabolism. Participants: One hundred and twenty-five nutrition professionals. Primary outcome: Knowledge and beliefs about inorganic nitrate. Results: Most nutrition professionals taking part in the survey had previously heard of inorganic nitrate (71%) and perceived it to be primarily beneficial (51%). The majority believed that nitrate consumption can improve sports performance (59%) and reduce blood pressure (54%), but were unsure about effects on cognitive function (71%), kidney function (80%) and cancer risk (70%). Knowledge of dietary sources of nitrate and factors affecting its content in food were generally good (41%–79% of participants providing correct answers). However, most participants were unsure of the average population intake (65%) and the acceptable daily intake (64%) of nitrate. Most participants (65%) recognised at least one compound (ie, nitric oxide or nitrosamines) that is derived from dietary nitrate in the body. Knowledge of nitrate, quantified by a 23-point index created by summing correct responses, was greater in individuals with a PhD (p=0.01; median (IQR)=13 (9–17)) and tended to be better in respondents with a masters degree (p=0.054; 13 (8–15)) compared with undergraduate-level qualifications (10 (2–14)). Conclusions: UK-based nutrition professionals demonstrated mixed knowledge about the physiology of dietary nitrate, which was better in participants with higher education. More efficient dissemination of current knowledge about inorganic nitrate and its effects on health to nutrition professionals will support them to make more informed recommendations about consumption of this compound.